2017
DOI: 10.1038/s41598-017-08535-4
|View full text |Cite|
|
Sign up to set email alerts
|

HDAC3 inhibition ameliorates spinal cord injury by immunomodulation

Abstract: Following spinal cord injury (SCI), the innate immune response of microglia and infiltrating macrophages clears up cellular debris and promotes tissue repair, but it also inflicts secondary injury from inflammatory responses. Immunomodulation aimed at maximizing the beneficial effects while minimizing the detrimental roles of the innate immunity may aid functional recovery after SCI. However, intracellular drivers of global reprogramming of the inflammatory gene networks in the innate immune cells are poorly u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
58
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(66 citation statements)
references
References 42 publications
8
58
0
Order By: Relevance
“…However, HDAC3 systemic pharmacological inhibition did not alter the extent of the CD11b‐positive inflammatory response around the injury site after spinal contusion (Kuboyama et al , ), in line with what we found here through intrathecal administration of RGFP966 after spinal dorsal hemisection. The same authors observed that systemic administration of RGFP966 did not affect neurite outgrowth of DRG neurons at 48 hours in culture (Kuboyama et al , ). This is in contrast to our findings showing that intrathecal delivery of RGFP966 promotes DRG regenerative growth in culture.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…However, HDAC3 systemic pharmacological inhibition did not alter the extent of the CD11b‐positive inflammatory response around the injury site after spinal contusion (Kuboyama et al , ), in line with what we found here through intrathecal administration of RGFP966 after spinal dorsal hemisection. The same authors observed that systemic administration of RGFP966 did not affect neurite outgrowth of DRG neurons at 48 hours in culture (Kuboyama et al , ). This is in contrast to our findings showing that intrathecal delivery of RGFP966 promotes DRG regenerative growth in culture.…”
Section: Discussionsupporting
confidence: 92%
“…It has also been shown that HDAC3 might control the expression of immune‐related gene targets in inflammatory models of SCI such as contusion injuries, where systemic pharmacological HDAC3 inhibition with RGFP966 was followed by improved functional recovery (Kuboyama et al , ). However, HDAC3 systemic pharmacological inhibition did not alter the extent of the CD11b‐positive inflammatory response around the injury site after spinal contusion (Kuboyama et al , ), in line with what we found here through intrathecal administration of RGFP966 after spinal dorsal hemisection. The same authors observed that systemic administration of RGFP966 did not affect neurite outgrowth of DRG neurons at 48 hours in culture (Kuboyama et al , ).…”
Section: Discussionmentioning
confidence: 99%
“…Primary microglia were isolated from the cerebral cortices of mice as previously described with minor modifications (Kuboyama et al, ). In brief, the cerebral cortices were dissected from ddY mice (Japan SLC, Hamamatsu, Japan) at postnatal Days 2–4, and the dura mater was removed.…”
Section: Methodsmentioning
confidence: 99%
“…Cells were seeded into 10‐cm dishes and cultured at 37°C with 10% CO 2 . After 14 days, microglial cells were isolated from mixed glial cultures with mild trypsinization (Kuboyama et al, ) and seeded into eight‐well slide at a density of 2.17 × 10 4 cells/cm 2 . To detect the effects of naringenin on polarization of normal cultured microglia and expression of Aβ degradation enzymes, cells were treated with naringenin (0.1–100 μM, Cat.…”
Section: Methodsmentioning
confidence: 99%
“…Resolution of arthritis is promoted by HDAC2's interaction with Tet2, leading to deacetylation and thus repression of the Il6 locus (82). HDAC3 inhibition also proved beneficial in spinal cord injury (136).…”
Section: The Journal Of Clinical Investigationmentioning
confidence: 99%